Analysis of Mobility Impacts on LTE Network for Video Streaming Services using Distributed Antenna System - Putri, Hasanah; Nopiani Damayanti, Tri; Tulloh, Rohmat (IJAIT (International Journal of Applied Information Technology), 2017)
LTE (Long Term Evolution) is a Broadband Wireless Access (BWA) technology that allows high speed and a wide range of access. LTE is designed to meet the needs for Quality of Service (QoS), i.e. the ability to download up to 300 Mbps and upload up to 75 Mbps. This study investigated the impacts of user mobility on the LTE network for video streaming services. The approach employed in this study included multi-user with Distributed AntennaSystem (DAS) and various variations of user mobility speed. Observations were made on the condition of the user moving from one cell to another so that the handover occurred. The throughput value will increase by 33% and 47% when the user’s distances are respectively 1250 m and 2000 m from eNode B. In addition, the delay value will reduce by 66.32% an 67.58% when the user’s distances are respectively 1250 m and 2000 m from eNode B. Moreover, the PDR value will increase by 48.74% and 55.45% when the user’s distances are respectively 1250 m and 2000 m from eNode B. The use of a distributed antenna system (DAS) model on LTE network has resulted in improved quality of performance when the user streams a video.